Muscle myosins form folded monomers, dimers, and tetramers during filament polymerization in vitro - Liu, Xiong (Proc Natl Acad Sci U S A, 2020)
Muscle contraction depends on the cyclical interaction of myosin and actin filaments. Therefore, it is important to understand the mechanisms of polymerization and depolymerization of muscle myosins. Muscle myosin 2 monomers exist in two states: one with a folded tail that interacts with the heads (10S) and one with an unfolded tail (6S). It has been thought that only unfolded monomers assemble into bipolar and side-polar (smooth muscle myosin) filaments. We now show by electron microscopy that, after 4 s of polymerization in vitro in both the presence (smooth muscle myosin) and absence of ATP, skeletal, cardiac, and smooth muscle myosins form tail-folded monomers without tail–head interaction, tail-folded antiparallel dimers, tail-folded antiparallel tetramers, unfolded bipolar tetramers, and small filaments. After 4 h, the myosins form thick bipolar and, for smooth muscle myosin, side-polar filaments. Nonphosphorylated smooth muscle myosin polymerizes in the presence of ATP but with a higher critical concentration than in the absence of ATP and forms only bipolar filaments with bare zones. Partial depolymerization in vitro of nonphosphorylated smooth muscle myosin filaments by the addition of MgATP is the reverse of polymerization.